Recent Advances in Targeted Drug Delivery Strategy for Enhancing Oncotherapy - Jianmin Li; Qingluo Wang; Guoyu Xia; Nigela Adilijiang; Ying Li; Zhenqing Hou; Zhongxiong Fan; Jinyao Li (Pharmaceutics, 2023)
Targeted drug delivery is a precise and effective strategy in oncotherapy that can accurately deliver drugs to tumor cells or tissues to enhance their therapeutic effect and, meanwhile, weaken their undesirable side effects on normal cells or tissues. In this research field, a large number of researchers have achieved significant breakthroughs and advances in oncotherapy. Typically, nanocarriers as a promising drug delivery strategy can effectively deliver drugs to the tumor site through enhanced permeability and retention (EPR) effect-mediated passive targeting and various types of receptor-mediated active targeting, respectively. Herein, we review recent targeted drug delivery strategies and technologies for enhancing oncotherapy. In addition, we also review two mainstream drug delivery strategies, passive and active targeting, based on various nanocarriers for enhancing tumor therapy. Meanwhile, a comparison and combination of passive and active targeting are also carried out. Furthermore, we discuss the associated challenges of passive and active targeted drug delivery strategies and the prospects for further study.